The impact of non-tariff barriers on maize and beef trade in East Africa - Karugia, Joseph T.; Wanjiku, J.; Nzuma, J.; Gbegbelegbe, Sika; Macharia, E.; Massawe, Stella C.; Freeman, H.A.; Waithaka, M.M.; Kaitibie, S. (Alliance for a Green Revolution in Africa and International Livestock Research Institute, 2011)
On March 2, 2004, the East African Community (EAC) member states signed the protocol for the establishment of the East African Community Customs Union, which commits them, among others, to eliminate non-tariff barriers (NTBs) to increase intraregional trade. However, several NTBs are still applied by member states, raising concerns among policy makers and the business community. There is, however, no information about the magnitude of the impact of these NTBs. This study identifies the existing NTBs on maize and beef trade in East Africa and quantifies their impact on trade and the welfare of EAC citizens using a Spatial Equilibrium Model (SEM). Data on NTBs were collected from traders and transporters of maize and beef cattle in East Africa. In addition, the study found that the main types of NTBs within the three founding members of the EAC (Kenya, Tanzania and Uganda) are similar. They include administrative requirements (mainly licenses, municipal and council permits), taxes/duties (mainly excise and cess duty), roadblocks, customs barriers, weighbridges, licensing, corruption (e.g., through bribes) and transiting. The results of the welfare analysis vary across the three countries, but the net monetary gains are positive in all cases. A complete abolishment or a reduction of the existing NTBs in maize and beef trade increases intra-EAC maize and beef trade flows, with Kenya importing more maize from both Uganda and Tanzania, while Uganda’s beef exports to Kenya and Tanzania increase. As a result, positive net welfare gains are attained for the entire EAC maize and beef sub-sectors. In all cases, those who gain from the proposed reductions in NTBs can potentially compensate the losers, leading to potential improvements in welfare. These findings give compelling evidence in support of the elimination of NTBs within the EAC customs union. The study recommends taking a regional approach to eliminating the existing NTBs since they are similar across the member countries and across commodities so as to exploit economies of scale. Other policy recommendations include streamlining of administrative procedures at border points to improve efficiency, and speeding up the implementation of procedures at point of origin and at the border points. Finally, the study recommends the need to design and implement monitoring systems to provide feedback to the relevant authorities on the implementation of measures to remove unnecessary barriers to trade within the EAC region.